Perluasan Brand sebagal Strategi Branding Peningkatan Reputasi Rumah Sakit - Mia Rahma Romadona (Jurnal Psikologi, 2012)
The hospital is an organization with branding strategy such as a brand extension of health services, as an effort to enhance its reputation in the community. This study uses a qualitative multiple case study approach that aims to identify and understand the dynamics of brand extension as a branding strategy of the three hospitals that issued the brand to improve its reputation. Tools for the data collected using semi-structured interviews, observation and document study to explore the branding strategies used in the expansion of the brand. Three private hospitals type B participated in this study. Those hospitals had already brand for their own enterphseses. The results of data analysis brand extension is used as a branding strategy has been able to enhance the reputation of a hospital for the better in society. Despite the marketing division is nothing new in the hospital but the improvement, expansion, creation and promotion of the hospital has been carried out. One is a brand extension to the extensions of health sen/ices are made based on the vision, mission, internal strengths hospitals, and patient expectations. Brand extension is performed also assist and facilitate the hospitals for health care product promotion services, so as to add a positive value for the hospital's reputation.